Synthesis and investigation of electrical and thermal properties of conducting polymer polypyrole and polypyrole / multiwall carbon nanotube composites - Shabestari, Afarin Bahrami (2012)
Conducting polymer materials based on Polypyrrole (PPy) and Polypyrrole/ Multiwall carbon nanotube (PPy/MWNT) nanocomposite were synthesis by using chemical reaction process. PPy/MWNT composites were prepared with different concentrations of MWNT ranging from 0% to 20%. X-ray diffraction (XRD) revealed that no crystalline peak appeared for PPy, because of its amorphous feature. The X-ray data of the composites showed spectra similar to those observed from the pure PPy matrix, indicating that PPy has completely covered the MWNT. The Fourier transform infrared spectroscopy (FTIR) spectra of PPy and PPy/MWNT composites demonstrated nearly identical numbers and positions of IR absorption bands because of the matrix layer of polypyrrole has absorbed most of the IR spectra. Results from field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) showed that the diameter of MWNTs has increased and confirmed the presence of carbon nanotubes inside the composite. The transport properties has been studied by measuring Hall mobility (μH) and Hall coefficient (RH) of polypyrrole and PPy/MWNT nanotubes samples with different MWNT concentration using van der Pauw technique. The μH decreased as below for samples with 0%, 4%, 8%, 12%, 16% and 20% MWNT content from 100 to 300K respectively: 40.987 to 16.231cm2/V.s, 20.291 to 14.329cm2/V.s, 17.992 to 2.891cm2/V.s, and 8.228 to 0.926cm2/V.s, 6.329 to 0.541cm2/V.s and 3.688 to 0.081cm2/V.s. The RH reduced for samples with 0%, 4%, 8%, 12%, 16% and 20% MWNT content from 100 to 300K respectively as below: 2163.944 to 68.989cm3/C, 12.797 to 0.303cm3/C, 8.099 to 0.254cm3/C, 1.432 to 0.042cm3/C, 0.956 to 0.023cm3/C and 0.463 to 0.003cm3/C. The magnetic field dependency of RH revealed that it was inversely proportional with the applied magnetic field. The RH reduced with applied magnetic field (1 to 10KG) from 86.59 to 6.863cm3/C, 21.105 to 2.707cm3/C, 7.5592 to 1.337cm3/C, 0.025 to 0.002cm3/C and 0.019 to 0.002cm3/C for the samples with 0%, 4%, 8%, 12%, 16% and 20% MWNT content respectively. The μH decrement with magnetic field (1 to 10KG) was as below: 188.118 to 15.162cm2/V.s, 62.673 to 8.048cm2/V.s, 79.112 to 14.114, 53.471 to 3.380, 0.535 to 0.051, and 0.492 to 0.054 for the samples with 0%, 4%, 8%, 12%, 16% and 20% MWNT content respectively. The electron paramagnetic resonance (EPR) results showed that the Peak-to-peak linewidth (>H") value decreased in the order PPy-MWNT-20wt% (37.606mT) > PPy-MWNT-16wt% (49.328mT) > PPy/MWNT-12wt% (95.970) > PPy/MWNT-8wt% (120.879mT) > PPy/MWNT-4wt % (139.926mT) > pure PPy (150.831mT) at room temperature. The measurement revealed that the spin concentration (Ns) of the PPy/MWNT with the various MWNT content was larger than that of the pure PPy (2.07×106, 3.42×106, 12.7×106, 30.7×106, 33.8×106 and 41.96×106 spin g-1 for 0%, 4%, 8%, 16% and 20% MWNT content). Thermal stability (decomposition temperature was 116.04, 120.69, 126.03, 128.86, 141.18 and 170.96oC for samples with 0wt%, 4wt%, 8wt%, 12wt%, 16wt% and 20wt% MWNT content) and also thermal diffusivity (0.103, 0.118, 0.141, 0.186, 0.224 and 0.265mm2/S for samples with 0wt%, 4wt%, 8wt%, 12wt%, 16wt% and 20wt% MWNT content respectively) of the composite increased with the decrease of the feeding mass ratio of pyrrole to MWNTs.